2015
DOI: 10.1038/sj.bdj.2015.436
|View full text |Cite
|
Sign up to set email alerts
|

A survey of dental school's emergency departments in Ireland and the UK: provision of undergraduate teaching and emergency care

Abstract: Outlines various aspects of emergency departments in dental schools.Outlines current curriculum details, teaching methods and undergraduate experience in emergency dental care across dental schools.Discusses the use of various triage systems in emergency departments in dental schools.Outlines the GDC's stance on emergency dental care education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…reported findings from a national survey assessing educational and clinical practices of urgent care clinics at all US dental schools. A similar study was conducted in Ireland and the United Kingdom by Anderson et al 13 . in 2015.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…reported findings from a national survey assessing educational and clinical practices of urgent care clinics at all US dental schools. A similar study was conducted in Ireland and the United Kingdom by Anderson et al 13 . in 2015.…”
Section: Introductionmentioning
confidence: 52%
“…in 2015. Although the majority of schools in both studies reported similarities in service hours, faculty coverage, and provision of patient care services, key differences in students’ educational experiences were identified across institutions, likely because of differences in healthcare systems 12,13 . Schools with traditional departments and graduate programs often excluded undergraduate dental students from oral surgery, endodontic, and pediatric emergency procedures.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations